Socioemotional skills of teachers and cooperative learning of advanced level students a center for Alternative Basic Education for Presidiaries. - Santana Pilco, Juana Rosa (2020)
The purpose of this study was to determine the relationship between the socioemotional skills of teachers and the level of cooperative learning of the students of the secondary level of CEBA Noé Moisés Dávalos Ybañez - Tacna, 2015. In the methodology, a type of observational, prospective research was applied. transverse cohort. The sample was made up of 19 teachers and 67 students. The instrument, for teachers, was considered the Bar-On test, which assesses social-emotional skills. A questionnaire aimed at students, to evaluate cooperative learning. With regard to the scope of research, research has focused on evaluating emotional intelligence and cooperative learning, to provide suggestions that educational institutions can develop; evidencing the relevance of the integral formation, through the affective dimension. It has been found that the development of socio-emotional skills is at a promedio or average level in 68.4% of teachers, the level of cooperative learning of students is regular with 40.3%, and that there is a significant difference in the intrapersonal, interpersonal skills, adaptability, stress management and general mood of teachers with cooperative learning levels of students at the advanced level of the CEBA. And it is concluded that there is a significant relationship between the socioemotional skills of the teachers and the level of cooperative learning of the students of the secondary level of CEBA Noé Moisés Dávalos Ybañez - Tacna.